Artemisia absinthium L. ethanol extract inhibits the growth of gastrointestinal cancer cells by inducing apoptosis and mitochondria-dependent pathway - Li, Ting; Yu, Shaoqi; Ma, Zihang; Li, Jinyao; Xia, Lijie; Feng, Yan (Frontiers in Oncology, 2025)
ObjectivesArtemisia absinthium L. has a long history in the treatment of gastrointestinal cancer (GIC), but its molecular mechanisms remain unclear.Materials and methodsWe identified and validated the active components and key targets in A. absinthium for the treatment of GIC by LC-MS and Network analysis. The antitumor effect of A. absinthium ethanol extract (AAEM-V) against gastrointestinal tract cancer in vitro and in vivo as well as the anticancer activity of the active ingredient, Luteolinidin, were further evaluated.ResultsAAEM-V exhibited good anticancer activity in vitro and in vivo. The active ingredient Luteolinidin was taken to intersect with the targets of gastric and colorectal cancers, and 69 common targets were identified. A total of three core targets, SRC, EGFR, and AKT1, were screened according to PPI and molecularly docked with Luteolinidin, and it was found that their binding played a key role in the treatment of tumors. Meanwhile, its active ingredient Luteolinidin was found to induce ROS proliferation to promote apoptosis and prevent cells from entering S phase.ConclusionThese findings not only explored the anti-gastrointestinal cancer chemical properties of A. absinthium, but also provided a new research direction for the active ingredients and mechanism of action of traditional Chinese medicine.